Effect of cotton fabric pretreatment on drop spreading and colour performance of reactive dye inks. (18th July 2016) - Liu, Zundong; Fang, Kuanjun; Gao, Hongguo; Liu, Xiuming; Zhang, Jianfei
Abstract : Ink dot distribution on cotton fabrics determines the colour performance of reactive dye inkjet printing, and ink drop spreading is one of the important factors influencing the ink dot distribution. In order to reveal the relationship between fabric pretreatment and ink drop spreading, two pieces of cotton fabric were pretreated respectively with sodium alginate and sodium alginate plus high fatty acid derivative solutions. Results indicate that the surface energy of the cotton fabrics was reduced from 73.79 to 69.45 and 58.49 mJ m −2 after the pretreatment with sodium alginate and sodium alginate plus high fatty acid derivative respectively. Correspondingly, the spreading area of cyan ink drops on these fabrics was reduced from 104.9 to 92.5 and 72.3 mm 2 . Furthermore, on the fabric treated with sodium alginate plus high fatty acid derivative, the strip‐like ink dots were narrow and short, which means the dye was concentrated in an area on the fabric surface. Colorimetric values of the inkjet‐printed fabrics demonstrated that the high fatty acid derivative would enhance the ability of sodium alginate to control ink droplet spreading, thereby improving the colour performance.